Kajian Kemitraan Agribisnis Kopi : Dampak Pendampingan terhadap Produktivitas Petani - Muhamad Nu’man Adinasa; Tintin Febrianti Tintin Febrianti; Asep Permadi Gumelar Gumelar (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
Coffee productivity among smallholder farmers in non-central producing regions like Samarang District, Garut Regency, is constrained by limited cultivation techniques, market uncertainty, and climate change threats. The agribusiness partnership between farmers and seed breeders offers a strategic solution, yet its effectiveness and managerial position have not been profoundly analyzed. This study aims to evaluate the strengths, weaknesses, opportunities, and threats (SWOT) of the coffee agribusiness partnership between farmers and seed breeders in Samarang, Garut, and to determine its strategic positioning for developing a sustainable partnership model. A quantitative approach with a survey method was employed. Samples were selected using purposive sampling, comprising 35 active coffee farmers in the Bina Bakti Farmers Group and 1 seed breeder. Primary data collected via structured questionnaires with a 1–5 Likert scale were analyzed using the weighted scoring method to map the SWOT matrix. The partnership performance evaluation demonstrated a significant positive impact, with farmers' yields increasing by 77.8% (from 851.56 kg to 1,513.83 kg) and incomes surging by 121.2% (from IDR 19.7 million to IDR 43.6 million). The SWOT quadrantal analysis indicated that Strengths were in the very high category (85.20), Weaknesses were low (34.18), Opportunities were moderately high (64.51), and Threats stood at a moderate-to-high level (58.78), with climate change impacts identified as the highest threat indicator. The strategic positioning of this partnership system lies in Quadrant I (Aggressive/SO Strategy).